PENGARUH LOVE OF MONEY, MACHIAVELLIAN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN EFEKTIVITAS PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI : STUDI EMPIRIS PADA OPD KAB. MALUKU TENGGARA - Jefry Gasperz; Franco Benony Limba; Aisyah Az Zahrah (LP2M Universitas Bina Bangsa, 2024)
This study aims to examine the effect of love of money and Machiavellian on the tendency of accounting fraud with the effectiveness of internal control as a moderating variable. Respondents in this study were employees of the Office and OPD Agency of Southeast Maluku Regency. The population in this study were all employees who worked at the Office and OPD Agency of Southeast Maluku Regency, the number of respondents who sampled this study were 130 people who worked at the Office and OPD Agency of Southeast Maluku Regency. The data collection method used in this study is to use the questionnaire method. This method uses the distribution of questionnaires to the sample and the sampling technique used is purposive sampling. While the data processing method used by researchers is Moderated Regression Analysis (MRA). The results of this study indicate that love of money and Machiavellian have a positive effect on the tendency of accounting fraud, while the effectiveness of internal control has no effect in moderating the effect of love of money and Machiavellian on the tendency of accounting fraud